Optimal levels of water and salt in the growth of giant sweet clone cactus forage (Research, Society and Development, 2021)
Forage cactus is perennial growth plant, resistance to drought adaptation to hot climate regions, being considered important for the development of livestock. In this study objective was estimate the morphometrics measures of forage cactus Giant Sweet clone associate the optimal levels water and salt. Design used was completely randomized, composed of four levels of water replacement, using the crop evapotranspiration (25, 50, 75 and 100%.Etc) and four levels of salinity (0, 2, 4 and 8 dS/m), obtained through the concentrations of (NaCl) salts corresponding to 0, 1.16, 2.32 and 4.64 g/L, respectively. The morphometric measures of cladodes were evaluated 20 times during the experimental period. Response surface was used to estimate the optimal levels water and salt that maximizing the morphometric measures of the cladodes. Water level in range of 54% and 64%, and 3.5 to 5.3 dS/m of saline level promote greater development of the Giant Sweet clone without changing the morphological characteristics of plant, generating greater phytomass yield.